Evalution of the inhibitory and lethal efficacy of Lavender Oil against Aspergillus niger and identify its effective components - جريكوس, بلسم (Latakia University Journal -Biological Sciences Series, 2023)
Balsam Jreikous □ABSTRACT□ In this research, the effect of different concentrations of Lavender oil on the growth of Aspergillus niger was studied, and all studied concentrations showed a clear inhibitory effect against this fungus. The inhibitory activity varied according to the different concentrations (0.06-0.04-0.03-0.02-0.006-0.004-0.002 ml/g) showed 100% inhibition against Aspergillus niger, and the inhibition percentage was 27.05% at 0.001ml/g and 3.52% at a concentration of 0.0002 ml/g on the seventh day of incubation. The lethal concentration (MBC) value of Lavender oil against Aspergillus niger was 0,02 ml/g . Chemical analyzes on the GC-MS chromatograph revealed the presence of 39 different compounds in Lavender oil ,and the following compounds were Linalool /4-Terpineol/Camphor /Acetic acid linalool ester/ Borneol /1.8-Cineole / β -Farnesene/ β -trans-Ocimene/dl-limonene/Butanoic acid/hexylester are the most concentrated,respectively.